The Relationship Between Emotional Intelligence and Adversity Quotient in Working Students: Hubungan Antara Kecerdasan Emosional dengan Adversity Quotient pada Mahasiswa Pekerja - Mulyasari, Pungky; Maryam, Effy Wardati (Universitas Muhammadiyah Sidoarjo, 2023)
This research is motivated by the phenomenon of the adversity quotient problem in working students which is characterized by a lack of enthusiasm for participating in the lecture process according to the adversity quotient aspect, namely endurance. In this case, the resilience of students to work is not reflected in facing their difficulties. Then often complain in lecture activities, including the aspect of the adversity quotient, namely control. This makes self-control in working students low, where working students cannot carry out their duties as working students. The purpose of this study was to determine the relationship between emotional intelligence and the adversity quotient of working students at the Muhammadiyah University of Sidoarjo. This research is a correlational quantitative research. The sample in this study was 251 students who were taken using the Incidental Sampling technique. The data collection technique used a psychological scale of emotional intelligence and adversity quotient which was arranged on a Likert scale. The data analysis technique for hypothesis testing was carried out with the Pearson Correlaton Product Moment. The results of this study indicate the correlation coefficient (rxy) = 0.411 (significance 0.000 <0.05). This means that there is a positive relationship between emotional intelligence and adversity quotient in student workers. The higher the emotional intelligence, the higher the adversity quotient, and vice versa. The determination test shows the effect of emotional intelligence on the adversity quotient of 16.8%.